Implementation of a Delirium Assessment Protocol in an Inpatient Hospice Setting. Issue 3 (June 2016) - Harrison, Alison; Smith, Robert; Champagne, Mary; Martin, Beth; Pursley, Jennifer; Hendrix, Cristina
Abstract : The purpose of this quality improvement project was to improve the recognition of delirium in an inpatient hospice setting through the use of the Confusion Assessment Method (CAM) by staff nurses. After receiving education on the CAM, staff nurses used the tool to assess for the presence of delirium among adult patients admitted for hospice care. Those who screened positive were further assessed for reversible causes of the syndrome with CHIMBOP (constipation, hypovolemia/hyponatremia, infection, medications, bladder catheter or obstruction, oxygen deficiency, and pain). After project implementation over 8 weeks, nurses completed an ease-of-use survey for the tool. Ninety-two percent of adult hospice patients eligible for delirium assessment were assessed by staff nurses. Of these, 36% screened positive for delirium. The ease-of-use survey indicated that approximately 30% of nurses strongly agreed or agreed that the CAM and CHIMBOP added value to their nursing practice. The results of this project indicated that nursing staff are able to assess for delirium in the inpatient hospice setting but most do not agree that the CAM and CHIMBOP add value in their practice.